Prevalence of Radiographic and Magnetic Resonance Imaging Features of Patellofemoral Osteoarthritis in Young and Middle‐Aged Adults With Persistent Patellofemoral Pain. Issue 8 (3rd July 2019) - Collins, Natalie J.; Oei, Edwin H. G.; de Kanter, Janneke L.; Vicenzino, Bill; Crossley, Kay M.
Abstract : Objective: To describe the prevalence of radiographic features of patellofemoral (PF) osteoarthritis (OA) in adults with persistent PF pain, to describe the prevalence of magnetic resonance imaging (MRI)–defined PF OA and compare it to that in age‐ and sex‐matched controls, and to explore the prevalence of radiographic and MRI‐defined PF OA across age, sex, and body mass index (BMI) groups. Methods: This cross‐sectional study included 84 individuals with PF pain ≥3 months duration and 26 age‐ and sex‐matched controls. In participants with PF pain, posteroanterior, lateral, and skyline radiographs were obtained. Radiographic OA features were scored using Kellgren/Lawrence (K/L) criteria and a radiographic atlas, with K/L grade ≥2 defined as OA, and K/L grade 1 as early OA. Both groups underwent 3.0 Tesla MRI scans, scored using the MRI Osteoarthritis Knee Score criteria. Compartmental prevalence of MRI OA features was based on cartilage lesions, bone marrow lesions (BMLs), and osteophytes. Results: Overall, 20 participants (24%) with PF pain had radiographic PF OA (K/L grade ≥2), and 36 participants (43%) had early PF OA (K/L grade 1). MRI‐defined PF OA was more prevalent in participants with PF pain (16–29%) than in controls (4–12%), irrespective of how PF OA was defined. Within the PF pain group, the prevalence of PF OA on radiographs and MRI was greater in participants who were older or female or who had a higher BMI. Conclusion: Features of radiographic and MRI‐defined PF OA were evident in 20–30% of adults ages 26–50 years with persistent PF pain, with greater prevalence observed in those who were older, or female, or who had a higher BMI. MRI‐defined PF OA was more prevalent in individuals with PF pain than in pain‐free controls, especially when defined as a full‐thickness cartilage lesion with BML.